COVID-19 and Ensuring Safe Cities and Safe Public Spaces for Women and Girls - ONU Femmes (United Nations, 2020)
The brief highlights emerging trends and implications for women and girls’ safety in cities and public spaces, recognizing the continuum of violence against women and girls in private and public spaces throughout different phases of the pandemic. It provides examples of concrete action taken at the local level in partnership with governments, grassroots women and women’s rights organizations, the private sector and other partners, including from cities participating in the UN Safe Cities and Safe Public Spaces Global Flagship Initiative, and in particular from cities where the disease is widespread. The brief includes recommendations to be considered by governments, international organizations, women’s rights and other civil society organizations. It is a living document that complements other policy briefs prepared by UN Women on COVID-19 (coronavirus) and ending violence against women. It draws upon the knowledge and experience of a wide range of experts who support solutions to end sexual harassment and other forms of violence against women and girls in urban, rural and online settings, attentive to the country context in which the crisis is occurring.